Psychometric properties of the Brazilian version of the lived experience component of the Spiritual Health And Life-Orientation Measure (SHALOM) - Nunes,Sandra Adriana Neves (2018)
Abstract This study had the following aims: (i) to translate the Spiritual Health and Life-Orientation Measure (SHALOM) into Brazilian Portuguese and adapt it to ensure the semantic/conceptual equivalence and content validity of the Brazilian version and (ii) to analyse the psychometric properties—reliability, convergent validity, discriminant validity and factorial validity—of the lived experience component, also called the Spiritual Well-Being Questionnaire (SWBQ), in a calibration sample and in a validation sample of Brazilian adults. The calibration sample comprised 436 subjects, 159 men and 277 women, aged between 18 and 79 years (mean age = 32.20 years; SD = 11.46); the validation study sample comprised 388 subjects, 253 women and 135 men, aged between 18 and 59 years (mean age = 30.59 years; SD = 9.44). All subjects completed a sociodemographic questionnaire, the Brazilian SWBQ and the Psychological Well-being Scale (PWBS). The results provide evidence of the reliability and factorial validity of an oblique four-factor model of a reduced 17-item version but revealed some problems with the convergent validity of the communal and personal factors (average variance extracted < .50). Nonetheless, these results provide evidence that the Brazilian version of the lived experience component of SHALOM (or SWBQb) has good psychometric properties and is a valid method of evaluating the spiritual health of Brazilian adults. Further research is required to establish the convergent and discriminant validity of this reduced version.